Without Assumptions: Development of a Socio-Emotional Learning Framework That Reflects Community Values in Cameroon - Anziom, Brigitte; Strader, Sarah; Sanou, Anselme Simeon; Chew, Philip (Frontiers in Public Health, 2021)
The mission of the Dɛngbɛ Bide (“Two Rabbits” in the Baka language) project in Cameroon is to support Baka communities to prepare children for success in formal school-based and traditional forest-based educations. The project develops curriculum for community-based preschools in the Baka language and cultural style, including a focus on Socioemotional learning (SEL). Socioemotional skills are key to achieving independence in adulthood. What skills help individuals succeed are closely related to societal values, environment and culture. Measures of SEL must therefore be adapted to the culture of the target population. Dɛngbɛ Bide developed a SEL measurement tool specific to the Baka context to achieve four objectives: 1) understand how Baka caregivers perceive SEL, 2) capture SEL development through a contextualized measure, 3) strengthen SEL components of the curriculum, and 4) measure student SEL growth. Dɛngbɛ Bide developed the SEL tool through a participative and interactive process. Using quick ethnography methodology and an emic approach, parents and other community members played a central role in each step of the tool development process. This process resulted in the production of a Parent tool and a Teacher tool to guide observation, monitoring and evaluation. These two tools are complementary, allowing Dɛngbɛ Bide to capture child behavior in the school and the home, and to collect data on all participating children within a specific time period. The described approach is simple, practical, based on the community context, and derived from to the local culture. The process for identifying SEL domains and the structure of questionnaire reflect community norms. This paper details the approach taken for developing culturally-adapted SEL measures, and contributes to the global body of research on SEL.